Time-dependent performance of ribbed plates on multi-layered fractional viscoelastic cross-anisotropic saturated soils. (April 2022) - Ai, Zhi Yong; Jiang, Yuan Hao; Zhao, Yong Zhi; Mu, Jin Jing
Abstract: The ribbed plate is divided into the rib-beams and the plate, in which the rib-beams are analyzed by the cross-beam theory, and the plate is assumed to be a Mindlin plate. The rib-beams and the plate are coupled to obtain the FEM stiffness matrix equation of the ribbed plate. The extended precise integration solution of multi-layered cross-anisotropic saturated soils with the fractional viscoelastic model is used as a fundamental solution of the BEM to obtain the soil stiffness matrix on the plate-soil interface. By introducing the compatibility conditions at this interface, the interaction equation between the soils and ribbed plate is achieved. Finally, by comparing the results from this theory and those from existing literatures and ABAQUS, the correctness of this method is proven, and the effects of the height and the layout of the rib-beams on the time-dependent behavior of ribbed plates on multi-layered fractional viscoelastic cross-anisotropic saturated soils are discussed.